2017
DOI: 10.1259/bjr.20160271
|View full text |Cite
|
Sign up to set email alerts
|

Blurred digital mammography images: an analysis of technical recall and observer detection performance

Abstract: According to this study, monitors ≤2.3 MP are not suitable for technical review of full-field digital mammography images for the detection of blur. Advances in knowledge: This research proposes the first observer standard for the visual detection of blurring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The study of Ma et al tended to agree with this and suggested that low resolution monitors are not suitable for the detection of blur. 23 In this study the comparison took place between two monitors with different specifications and 2.3 and 5 MP resolution respectively. It appeared that the monitor with 2.3 MP resolution had poorer visual detection for blur and consequently higher technical recall rate than the higher resolution monitor.…”
Section: Articles Addressing Monitor Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Ma et al tended to agree with this and suggested that low resolution monitors are not suitable for the detection of blur. 23 In this study the comparison took place between two monitors with different specifications and 2.3 and 5 MP resolution respectively. It appeared that the monitor with 2.3 MP resolution had poorer visual detection for blur and consequently higher technical recall rate than the higher resolution monitor.…”
Section: Articles Addressing Monitor Specificationsmentioning
confidence: 99%
“…Ma et al, 2017, [23] Blurred digital mammography images: An analysis of technical recall and observer detection performance UK 5 MP monitor better for blur detection on mammographic images…”
Section: Ukmentioning
confidence: 99%
“…Often blur fails to be detected at the time of imaging, and it might not be detected until it reaches the reporting room for diagnostic examination. 9 While there have been studies investigating radiologists' ability to detect blur visually in mammograms, as of this date there is no work done on detecting blur automatically in mammograms except the work presented by Hill et al 8 In addition, there has been no effort to use machine-learning algorithms to automatically detect blurry mammograms. Instead of relying on the radiologists' subjective assessments of the presence or absence of blur in mammograms, we propose the use of quantitative mathematical features that quantify blur objectively in digital mammograms.…”
Section: Introductionmentioning
confidence: 99%
“…False‐negative decisions could have implications in clinical practice. Often blur fails to be detected at the time of imaging, and it might not be detected until it reaches the reporting room for diagnostic examination . While there have been studies investigating radiologists' ability to detect blur visually in mammograms, as of this date there is no work done on detecting blur automatically in mammograms except the work presented by Hill et al In addition, there has been no effort to use machine‐learning algorithms to automatically detect blurry mammograms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation